Metabolic Cost Reduction and Analysis of Assisted Walking Gait: A Review - Shehab, Noor Abdul Kareem; Ismail, Mahmud Rasheed (Al-Nahrain Journal for Engineering Sciences, 2025)
With the occurrence of pathological disorders in some people or aging, metabolic energy consumption begins significantly due to the weakness of the peripheral muscles and the increase in body fat with time, which aggravates the issues for this type of people, causing the rest hours extremely lengthy and consequently may produce heart or arterial diseases and elevate the mortality rate. Regarding the significance of the matter, this study examines a number of previous researches that featured several approaches to energy calculation and strategies for lowering energy consumption through the use of various external assistance devices, such as exosuits or exoskeletons, to assist people in carrying out their everyday tasks. And additionally discussed musculoskeletal simulation employs a variety of programs, especially OpenSim, which enables users to build models of musculoskeletal structures and produce dynamic movement simulations. According to the research findings, exoskeletons and other assistive technology can successfully lower the cost of metabolic energy to varying extents, depending on the device’s weight, placement within the body, and whether it is active, semi-active, or inactive. In the future, the work to design and simulate a semi-active torsional ankle-foot exoskeleton with a specialized mechanism aimed to minimize metabolic energy.